Therapeutic Potential of Cilostazol in Aneurysmal Subarachnoid Hemorrhage: A Systematic Review - Felicia, Felicia; Jaya, Michael (Jurnal Neuroanestesi Indonesia, 2025)
Introduction: Vasospasm and delayed cerebral infarction (DCI) are factors that influence the prognosis and clinical outcomes in subarachnoid hemorrhage (SAH). Although several pharmacological therapies are considered potentially effective in reducing vasospasm and DCI, only a few have shown significant benefits. This systematic review aims to evaluate the therapeutic benefits of cilostazol in patients with aneurysmal subarachnoid hemorrhage (aSAH). Subject and Methods: A systematic search was conducted on studies from January 2009 to March 2024 across five databases, guided by PRISMA 2021. The outcomes evaluated may include angiographic vasospasm, symptomatic vasospasm, the severity of vasospasm, new cerebral infarctions, delayed cerebral ischemia, and functional outcomes. Results: Following analysis, 9 studies were included in this systematic review, involving 627 patients in the cilostazol group and 631 patients in the control group. Most of these studies indicated that cilostazol administration in SAH yielded positive effects on cerebral vasospasm, new infarctions, and functional outcomes. However, there was no evidence to support the effectiveness of cilostazol in preventing DCI. Conclusion: Overall, cilostazol appears to be a promising therapy for SAH. However, the impact of cilostazol on DCI warrants further investigation, possibly due to the complex mechanisms of DCI.